2015
DOI: 10.1007/s00420-015-1081-7
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in finger blood flow induced by 125-Hz vibration: effect of location of contact with vibration

Abstract: Differences in vasoconstriction between subjects and between locations are consistent with the Pacinian channel mediating both absolute thresholds and vibration-induced vasoconstriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The findings are consistent with Ekenvall et al ( 1989 ) who found no relation between vascular symptoms and the outcome of sensory testing. Whereas the chronic changes giving rise to finger blanching are not clearly associated with thresholds, acute reductions in finger blood flow caused by vibration are associated with thresholds for the perception of vibration (Ye and Griffin 2011 , 2014 , 2016b ). The contradiction implies that the acute and chronic changes have different mechanisms, with the vascular impairment in vibration-exposed persons being associated with either a different form of neurological damage or some form of local structural damage causing the vascular phenomenon known as vibration-induced white finger.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with Ekenvall et al ( 1989 ) who found no relation between vascular symptoms and the outcome of sensory testing. Whereas the chronic changes giving rise to finger blanching are not clearly associated with thresholds, acute reductions in finger blood flow caused by vibration are associated with thresholds for the perception of vibration (Ye and Griffin 2011 , 2014 , 2016b ). The contradiction implies that the acute and chronic changes have different mechanisms, with the vascular impairment in vibration-exposed persons being associated with either a different form of neurological damage or some form of local structural damage causing the vascular phenomenon known as vibration-induced white finger.…”
Section: Discussionmentioning
confidence: 99%
“…The tails of rats in the vibrated group were exposed to sinusoidal vibration (250 Hz, 49 m/s 2 rms) for 4 h/day for 10 consecutive days. This frequency and amplitude was chosen because vibration with these characteristics generate resonance in the rat tail (23) Previous studies have shown that exposure at this frequency has the greatest effect on peripheral vascular and sensorineural function (26, 39), and this is the frequency at which the Pacinian corpuscles are most sensitive (13, 40). A description of the shaker and vibration control system was previously published (23).…”
Section: Methodsmentioning
confidence: 99%
“…These acute and repeated disturbances of different physiological parameters controlling vasoregulation can then accumulate chronically and lead to the occurrence of VWF. The exact mechanisms leading to permanent vascular changes still remain poorly understood [22,34]. In our study, we consider only the indirect neuronal mechanisms of the imbalance of vasoregulation.…”
Section: The Original Strategy Implementedmentioning
confidence: 99%